2012
DOI: 10.1016/j.jaut.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of TWEAK in lupus nephritis: A bench-to-bedside review

Abstract: There is significant unmet need in the treatment of lupus nephritis (LN) patients. In this review, we highlight the role of the TWEAK/Fn14 pathway in mediating key pathologic processes underlying LN involving both glomerular and tubular injury, and thus the potential for renal protection via blockade of this pathway. The specific pathological mechanisms of TWEAK – namely promoting inflammation, renal cell proliferation and apoptosis, vascular activation and fibrosis – are described, with supporting data from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 142 publications
(243 reference statements)
1
81
0
1
Order By: Relevance
“…TWEAK may activate the NF-κB signaling pathway through binding with the Fn14 receptor, which may represent an underlying mechanism regarding LN activity status (18). A previous study has indicated that TWEAK is associated with LN activity (19); however, the specific mechanism involved remains unclear. Thus, the present study aimed to investigate the roles of TWEAK and the NF-κB signaling pathway in LN.…”
Section: Introductionmentioning
confidence: 99%
“…TWEAK may activate the NF-κB signaling pathway through binding with the Fn14 receptor, which may represent an underlying mechanism regarding LN activity status (18). A previous study has indicated that TWEAK is associated with LN activity (19); however, the specific mechanism involved remains unclear. Thus, the present study aimed to investigate the roles of TWEAK and the NF-κB signaling pathway in LN.…”
Section: Introductionmentioning
confidence: 99%
“…Other than its known expression in endothelial cells 8 and fibroblasts, 9 we recently found expression of Fn14 on mesangial cells, podocytes, and tubular cells, whereas functional studies have implicated TWEAK/Fn14 signaling in the pathogenesis of renal disease. [9][10][11] Previously, we showed that TWEAK induces human kidney mesangial cells, tubular cells, and podocytes to express multiple inflammatory mediators, including RANTES, MCP-1, IP-10, ICAM-1, and VCAM-1, thus promoting kidney infiltration of inflammatory cells and stimulating cellular proliferation. 12,13 In chronic graft-versus-host disease, mice treated with an anti-TWEAK mAb had significantly diminished proteinuria and decreased kidney expression of proinflammatory cytokines.…”
mentioning
confidence: 99%
“…Involvement of the TWEAK/Fn14 axis in both glomerular and tubular damage positions this pathway as an attractive therapeutic target for the treatment of patients with LN, many of whom currently rely on broadly immunosuppressive agents [9]. CI, confidence interval; CL, clearance; CL 2 , intercompartmental clearance; Correlation V/CL, correlation between random effects of V and CL; dCLdBodyWeight, effect of body weight on CL; dVdBodyWeight, effect of body weight on V; dVdFemale, effect of sex on V; K m , Michaelis-Menten constant; Omega for each parameter, between-subject variability (standard deviation of the interindividual variability distribution) for the respective parameter; SD, standard deviation; Stderr, standard error; stdev0, estimated standard deviation for the normal residual error; tv, typical value for the respective pharmacokinetic parameters; V, distribution volume of the central compartment; V max , maximum elimination rate; V 2 , distribution volume of the peripheral compartment.…”
Section: Figurementioning
confidence: 99%
“…The TWEAK/Fn14 axis has been implicated in the pathogenesis of lupus nephritis (LN) [9,10], a serious complication of systemic lupus erythematosus (SLE), which is associated with high incidences of morbidity and mortality [11,12]. Expression of TWEAK and Fn14 is elevated in the kidneys of patients with LN, and the TWEAK/Fn14 pathway has been linked to several processes that underlie LN, including inflammation, vascular activation, mesangial cell proliferation, renal cell death and fibrosis [9,10,13].…”
Section: Introductionmentioning
confidence: 99%